Evaluation of Clinical Activities by Nurses Through Time Study - Chatitze Chousein; Manar Aslan (Association of Nurse Managers, 2022)
Aim: The research was conducted to determine how nurses use their time in a state hospital. Method: The research was conducted with the observation method in four selected wards of a provincial public hospital between 21.01.2019-28.06.2019. The observations were made by the researcher by recording the daily activities of the nurses, which were created as a result of the literature review, into three groups (direct, indirect, and personal). The research was conducted with a total of 30 high school, associate, and undergraduate graduate nurses working in the pediatric health and diseases service (8 nurse), orthopedics and traumatology (7 nurse), chest diseases (8 nurse), and cardiology and cardiovascular surgery (7 nurse) each were observed three times. Results: As a result of the observations, 87 different activities and a total of 3659 activities were carried out. It has been determined that 55.1% of these activities are direct activities, 16.6% are indirect activities and 27.9% are personal activities. It was observed that the most frequently repeated activity was chatting with friends, the most repeated activity groups were personal and direct activities, and the most frequent activity was the pediatric service. Considering their educational status, it was concluded that nurses with undergraduate degrees perform more direct, indirect and personal activities. Conclusion: As a result, it was found that the activities carried out by the nurses and the time they allocated to these activities varied according to the care needs and intensities of the services they worked.